Effect of Intercrops on the Incidence of Antigastra catalaunalis (Duponchel) (Crambidae: Lepidoptera) Infesting Sesame - Kalathiya, S. B.; Chandaragi, M. K.; Panickar, Bindu K.; Shinde, Manisha S. (International Journal of Bio-resource and Stress Management, 2025)
A field experiment was conducted at Agronomy Instructional Farm, Sardarkrushinagar Dantiwada Agricultural University, Sardarkrushinagar, North Gujarat, India during July to October, 2023 aimed to evaluate the effect of intercrops on the incidence of Antigastra catalaunalis (Duponchel) (Crambidae: Lepidoptera) infesting sesame. The trial was laid out in Randomized Block Design (RBD) with seven treatments viz., sesame (sole crop), sesame+black gram, sesame+pearl millet, sesame+cowpea, sesame+sorghum, sesame+cluster bean and sesame+marigold. The six treatments of these different intercrops were compared with sole sesame on the incidence of Antigastra catalaunalis larval population, its web infestation, capsule damage and seed yield. The results of the study revealed that sesame+cowpea treatment was found most effective in terms of reducing the larval population (0.73 larvae plant-1), web infestation (0.42 webs plant-1) and capsule damage (3.42%) due to leaf webber and capsule borer. It was followed by sesame+pearl millet treatment recorded minimum larval population (0.87 larvae plant-1), web infestation (0.52 webs plant-1) and capsule damage (4.00%). These two treatments are found significantly superior and are at par with each other. The highest sesame equivalent yield was obtained from the treatments sesame + marigold (1467 kg ha-1), sesame+pearl millet (892 kg ha-1) and sesame+cowpea (881 kg ha-1), respectively. These intercrops can be utilized for management of leaf webber and capsule borer, A. catalaunalis infesting sesame.